Prevalence of Ocular Hypertension in Patients Above 40 Years of Age - Parajuli, Sanket; Shrestha, Pooja; Sharma, Sadhana; Shrestha, Jeevan K (Nepalese Journal of Ophthalmology, 2022)
Introduction: Ocular hypertension is a condition with elevated intraocular pressure that needs to be monitored closely to prevent glaucoma and other complications. The study aims to find out the prevalence of ocular hypertension in patients aged more than 40 years.Materials and methods: This is a hospital based cross-sectional study conducted in a community based tertiary hospital of Nepal. Results: Mean age of the patients was 47.53years. 62% of the patients were males and 38% were females. Mean intraocular pressure in the right eye was 15.8 mmHg and mean intraocular pressure in left eye was 16.2 mm Hg. Prevalence of ocular hypertension was 6%.Conclusion: All patients more than 40 years of age should undergo detailed ocular examination for early detection and treatment of ocular hypertension.